Scientific Creativity in Materials Science Education among High School Students through Inquiry-Based Learning and Metacognitive Strategies - Pathomphong Boonpratham; Bovornpot Choompunuch; Hisako Matsuo (ASEAN Journal for Science and Engineering in Materials, 2027)
Materials science education requires high school students to connect abstract scientific concepts with the behavior and technological applications of materials. This study examined the effectiveness of inquiry-based learning integrated with metacognitive strategies in developing scientific creativity through electrostatics learning. A quasi-experimental two-group pretest–posttest design involved Grade 11 students assigned to experimental and control groups. The experimental group completed inquiry-based instruction incorporating planning, monitoring, and evaluating strategies, while the control group received conventional instruction. Scientific creativity was assessed through fluency, flexibility, and originality. ANCOVA results showed significantly higher adjusted posttest scores for the experimental group across all dimensions. The findings demonstrate the potential of inquiry–metacognition integration for fostering scientific creativity in materials science-oriented high school education.